Questioning laughter and obscenity in Berta & Isabo: um fragmento pornogeriatrico rural, by Hilda Hilst - Pugina, Rosana Leticia [UNESP]; Camara, Yls Rabelo (Univ Caxias Sul, Graduate Program Literature Culture & Regions, 2021)
Hilda Hilst presents elements of laughter and obscenity that challenge gender restrictions historically imposed on women by patriarchy. To elucidate that issue, the dramatic text Berta & Isabo: a Rural Pornogeriatric Fragment was selected. As an objective, we seek to understand the phonic and carnivalized constitution of the characters, elderly and sexually active women, in contrast to the standard built around female old age. Regarding the theoretical framework, we used the reflections of Bakhtin (1987) Maingueneau (2010) Moraes (2015) and Beauvoir (1967, 2018). Regarding the methodology, it is exploratory, qualitative and bibliographic. As a result, it appears that carnival, laughter and obscenity guide the creation of an inverted hierarchical thought in the studied Hilstian work, which overcomes intimidation and censorship, especially regarding the exercise of female sexuality in old age.
Keywords: Hilda Hilst; Laughter and obscenity; Pornographic discourse; Female emancipation in old age